Fear of dying in relation to religiosity in adults - Démuthová, Slavka; Bucik, Valentin (Studia Psychologica: Theoria et praxis, 2013)
The primary goal of this pilot study is to examine the relationship between the fear of dying and religiosity. The religiosity is seen as a complex concept of religious orientation. In addition to testing the relationship between the fear of dying and the religiosity itself, religious orientation (intrinsic vs. extrinsic), age, sex of subjects, and subjects’ experience with death of somebody close to them were tested. Subjects were Slovak male (N = 24, 38.1%) and female participants (N = 39, 61.9%) aged 19 to 69 (M = 39.62; SD = 14.76) from various social and educational backgrounds. Subjects with dominant intrinsic religious orientation (N = 31; 51.67%) reported significantly lower fear of one’s own dying (U = 232; p < .001). Intrinsic religiosity is negatively correlated (r = -.33, p < .01) with the fear of one’s own dying. We didn´t find statistically significant differences in fear of dying between believers and nonbelievers, men and women, younger and older subjects, subjects with and without experiences with death of somebody close to them. The important finding is, that the difference between the fear of one’s own death and death of somebody else was statistically significant in all studied groups. Therefore, the attention should be paid not only to the variables influencing the level of fear of dying but also to that whose dying evokes fear.